A organização do lazer e seus prazeres: um estudo de caso sobre o Club Med no Brasil - Brandão, Aline Lima (2009)
The research 'The organization of leisure and pleasure: the case of Club Med' takes tourism as a social practice. It’s look for understand local and global interaction’s in cultural dynamics. The Club Med’s case allows us to analyse comparatively the phenomenon of leisure hotels in Brazil and other countries. The goal is to know / understand (?) how these hotels becomes playful spaces around the world. At the same time / In addition (?), the study also includes the perspective of the customer and, consequently, the issue of consumption of the product resort in our contemporary society.